Dose‐Dense FEC Followed by Dose‐Dense Ixabepilone as Neoadjuvant Treatment for Breast Cancer Patients: A Feasibility Study. (12th August 2013) - Clavarezza, Matteo; Bordonaro, Roberto; Daniele, Bruno; Ferrandina, Gabriella; Barni, Sandro; Turazza, Monica; Coati, Francesca; De Matteis, Andrea; De Placido, Sabino; Cognetti, Francesco; Olmeo, Nina Antonina; Carrozza, Francesco; et al.
Abstract : Background: Ixabepilone is an effective chemotherapy in metastatic breast cancer that has been pretreated with anthracyclines and is resistant or refractory to taxanes. Adjuvant dose‐dense (DD) chemotherapy is more effective than regimens administered every 3 weeks, especially in hormonal receptor (HR)‐negative tumors. Methods: A feasibility study of neoadjuvant DD ixabepilone was conducted in breast cancer patients with tumors measuring at least 2 cm. Patients received 5‐fluorouracil 600 mg/m 2, epirubicin 90 mg/m 2, and cyclophosphamide 600 mg/m 2 ("FEC" in combination) administered intravenously on day 1 every 14 days with granulocyte‐colony stimulating factor (filgrastim) followed by ixabepilone 40 mg/m 2 administered intravenously on day 1 every 14 days with granulocyte‐colony stimulating factor. The study's primary endpoint was feasibility, and the secondary endpoint was pathologic complete response. A two‐stage Simon's design was adopted. Results: Forty‐seven patients were enrolled, and 42 were evaluable. For 10 of 42 patients, DD ixabepilone was not feasible. Six (14%) required ixabepilone interruption, and four (9.5%) required ixabepilone dose reduction of 25%. One toxic death occurred. Hematologic grade 3–4 toxicities included anemia (9.5%), grade 4 neutropenia (2.4%), febrile neutropenia (4.8%), and thrombocytopenia (2.4%). Nonhematologic grade 3–4 toxicities consisted of fatigue (14.3%), mucositis (14.3%), sensory neuropathy (7.1%), onychopathy (7.1%), and liver toxicity (4.8%). Grade 2 sensory neuropathy lasting longer than 7 days was recorded in 11.9% of patients. Pathologic complete response was observed in 16 of 42 patients (38.1%), including 11 of 23 (47.8%) with HR‐negative tumors and 5 of 19 (26.3%) with HR‐positive tumors. Conclusion: Despite high activity, DD ixabepilone after DD FEC is poorly tolerated. Abstract : 摘要 背景 . 对既往曾接受蒽环类并且对紫杉类耐药或紫杉类难治性转移性乳腺癌患者而言，伊沙匹隆是一种有效的化疗。辅助剂量密集（DD）化疗比每三周一次给药方案更加有效，尤其对激素受体（HR）阴性的肿瘤。 方法 . 我们在肿瘤≥2 cm的乳腺癌患者中开展了一项新辅助DD伊沙匹隆治疗的可行性研究。给予患者5‐氟尿嘧啶600 mg/m 2 、表柔比星90 mg/m 2 和环磷酰胺600 mg/m 2 （FEC方案），第1天静脉注射，14天为1周期；粒细胞集落刺激因子（非格司亭），序贯伊沙匹隆40 mg/m 2 ，第1天静脉注射，14天为1周期。研究的主要终点是可行性，次要终点为病理学完全缓解。采用Simon's二阶段设计。 结果 . 纳入47例患者，42例可评估。在42例患者中有10例不可使用DD伊沙匹隆。6例（14%）需要中断伊沙匹隆治疗，4例（9.5%）需要下调25%的伊沙匹隆剂量。发生了1例毒性死亡。3 ∼ 4级血液学毒性包括贫血（9.5%）、4级中性粒细胞减少（2.4%）、中性粒细胞减少性发热（4.8%）和血小板减少（2.4%）。3/4级非血液学毒性包含乏力（14.3%）、粘膜炎（14.3%）、感觉神经病变（7.1%）、甲病（7.1%）和肝脏毒性（4.8%）。11.9%的患者报告了持续时间超过7天的2级感觉神经病变。42例患者中有16例（38.1%）观察到病理学完全缓解，包括23例HR阴性肿瘤患者中的11例（47.8%）和19例有HR阳性肿瘤患者中的5例（26.3%）。 结论 . 尽管DD伊沙匹隆具有较高的抗肿瘤活性，但该方案序贯于DD FEC的耐受性差。 The Oncologist 2013;18:924‐925.